Les agglomérations indigénes de la péninsule ibérique chez Tite-uve - Estelle Bedon (Gerión, 2003)
Livy gives the names of about fifty Hispanic urban centres. It is relatively easy to identify o the main towns among them, but the information about secondary urban areas is too incomplete for a reconstruction of the urban hierarchy to be possible. This corpus also enables us to get a more definite idea of Livy’s rigour in his use of the terms referring to the various urban categories, i.e. turres, arces, vici, costella, oppido, urbes and civitates.